Africa's Development Debts. (8th November 2021) - Ndulu, Benno J; O'Connell, Stephen A
Abstract: Public debt levels in sub-Saharan Africa rose sharply in the wake of the global financial crisis, and a number of countries are now classified by the World Bank and International Monetary Fund as at high risk of debt distress. By contrast with the debt crisis of the 1980s and 1990s, however, concerns were not region wide as recently as early 2020, and the policy environment for growth remains robust for the majority of countries in the region. The external environment nonetheless poses a set of region-wide risks that include the economic effects of the COVID-19 pandemic and are exacerbated by the increase in market-based debt and the retreat of the Paris Club among official creditors. Changes in perceived creditworthiness can now drive distress, and new challenges of creditor coordination will complicate the debt restructuring process. We motivate a research agenda that focuses on development assets at risk as rising debt service obligations crowd out development as well as operational and maintenance budgets. Preserving and enhancing these assets, which include advances in human capital and infrastructure and an improved investment environment, should be a central objective of domestic policy actions, preventative debt restructurings and institutional approaches to debt distress.